Kajian Makna Simbol Kupu-Kupu Terbang ke Langit pada Tarekat QÃ¢dirÃ®yah NaqshabandÃ®yah Suryalaya Tasikmalaya - Kurnianto, Rido (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The Suryalaya Tarekat QÃ¢dirÃ®yah NaqshabandÃ®yah (TQN) has successfully attracted most people and some of which pointed as the alternative spirituality searching for the modern humans. The Suryalaya TQN has a unique symbol in the form of butterfly, which then underlies all activities of the Suryalaya TQNâs Boarding School. The article aims at answering a question on âwhat is the meaning of the Suryalaya TQNâs butterfly symbol?â In doing so, the study employs Turnerâs model of interpretive paradigm along with âprocessual symbologyâ approach. The study finds that: (1) Three dominant symbol characteristics shown by Turner have an intersection to the nature of the symbol used by the Suryalaya TQN, namely the condensation of many meanings, the unification of those different meanings and the polarization of the meanings, (2) Symbol has a meaning to the living dreams and hopes as well as refers to the stages of life whether as Godâs servant or as His khalÃ®fah/messenger, (3) The butterfly symbol is closely linked with the remembrance procession on the metamorphosis process, i.e. takhallÃ®, tahallÃ®, and tajallÃ®, (4) The interpretation of the butterfly symbol grows the concepts of Sufism such as sincerity, patience, mortality, belief, husn al-zann (positive thinking), and rajÃ¢â.Â